노인들의 질환별 유병여부와 건강관련 삶의 질 구조모형 분석 - 이동호(Dong-Ho Lee); 빈성오(Sung-Oh Bin) (한국콘텐츠학회 논문지, 11(1), 2011)
This study conducted a secondary analysis by using original data of <The Third Korea National Health and Nutrition Examination Survey, 2005> performed by Korea Institute for Health and Social Affairs to determine factors affecting health-related quality of life in the elderly. The results were as follows. For medical health condition, it became longer in endocrine diseases and cardiovascular diseases. In the case of functional health condition, subjects with musculoskeletal diseases showed higher functional health condition. Subjective health condition, while it became worse in digestive diseases and musculoskeletal diseases in the order, it recorded the best score when subjects did not have any musculoskeletal disease. Quality of life, while it became lower in endocrine diseases in the order, it was the highest when subjects did not have any musculoskeletal disease. Thus, increase of subjective health status for the elderly is important in the future. 본 연구는 한국보건사회연구원의 <2005년 국민건강영양조사 제 3기> 원 자료를 이용하여 노인들의 건강관련 삶의 질의 결정요인을 파악하기 위하여 이차분석을 실시하였다. 연구 결과는 다음과 같다. 첫째, 만성질환유무별 이환일수로 살펴본 의학적 건강상태에서 내분비계 질환의 유병이 많은 것으로 나타났다. 활동제한 년수로 측정한 기능적 건강상태에서는 근골격계 질환이 있을수록 활동제한 년수가 많은 것으로 나타났다. 주관적 건강상태에서 소화기계 질환, 내분비계 질환 순으로 건강상태가 나쁜 반면에 근골격계 질환이 없는 경우 건강상태가 가장 좋았다. 삶의 질에서는 내분비계 질환이 있을 경우 삶의 질이 낮았으며, 삶의 질에 대한 변수들의 효과에서는 주관적 건강상태가 가장 큰 효과를 보였다. 따라서 노인들의 주관적 건강상태를 높이는 것이 무엇보다도 중요하다고 할 수 있겠다.